PENERAPAN MEDIA SMART BOX MELALUI MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS IV - Desi Desi; Heny Kusuma W; Hani Prasetyaning Astuti (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The low interest and learning outcomes of students in Pancasila Education material are due to the limited use of innovative learning media. This issue serves as one of the research backgrounds, aiming to improve Pancasila Education learning outcomes through the use of Smart Box media for fourth-grade students at SD Negeri Sewulan 02. This research employs a classroom action research (CAR) method using the Kurt Lewin model, which consists of two cycles. Each cycle involves four stages: planning, implementation, observation, and reflection. The research subjects were 14 fourth-grade students in the 2024/2025 academic year. Data were collected through observations, tests, and interviews with the fourth-grade teacher as the teaching facilitator. The results of the study showed an increase in the percentage of student learning mastery. In the pre-cycle stage, student learning mastery only reached 35%. After the application of the Smart Box media, student mastery increased to 57% in the first cycle, and then reached 86% in the second cycle. Based on the achievement of 86% mastery in the second cycle, it can be concluded that the use of Smart Box media is effective in improving student learning outcomes. Additionally, the use of this media also increased students' enthusiasm during the Pancasila Education learning process, as evidenced by their active participation in learning activities and higher interest in the material being presented.